Expanding the Applications of the Profunda Artery Perforator Flap. Issue 2 (February 2016) - Mayo, James L.; Canizares, Orlando; Torabi, Radbeh; Allen, Robert J.; Hilaire, Hugo St.
Abstract : Background: The profunda artery perforator free flap has not gained traction for nonbreast reconstruction, likely because of the presence of a proven workhorse in the anterolateral thigh flap. The authors believe that the profunda artery perforator flap offers similar coverage characteristics with the benefits of a medial donor site, a more consistent anatomy, and relatively easy dissection. The authors review their indications, technique, and outcomes in seven patients requiring eight free flap reconstructions. Methods: The authors applied the use of the vertically oriented profunda artery perforator flap to both lower extremity and head and neck reconstructions in which an anterolateral thigh flap would normally have been used. Details reviewed include soft-tissue defect, perforator location, flap size, recipient vessel, and complications. Results: Eight soft-tissue defects were covered with a vertically oriented profunda artery perforator flap in seven patients. Six reconstructions were for distal lower extremity and two were for head and neck reconstruction, both trauma and oncologic reconstructions. Flap sizes ranged from 40 to 92 cm 2 . The pedicle length ranged from 7 to 10 cm. There were no partial or complete flap losses. One complication of seroma at the donor site requiring washout and closure was encountered. Conclusions: The profunda artery perforator flap is a safe and effective option for perforator-based free flap reconstruction with relative ease of harvest and an inconspicuous donor site. This flap offers an excellent alternative to the anterolateral thigh flap. In certain patient demographics, the profunda artery perforator flap should be considered as a primary option. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.